Effects of channel models and optional data rates on the IEEE 802.15.4a system performance - Findikli, C.; Erkucuk, S. (IEEE, 2010)
The wireless personal area network standard IEEE 802.15.4a uses ultra wideband impulse radios (UWB-IRs) for precise ranging and location, and as well as for communications at low data rates (about 1 Mb/s). In addition to low data rates, there are optional data rates defined in the standard that can support up to 27Mb/s. In this paper, the IEEE 802.15.4a system performance is studied for optional data rates in addition to considering the effect of channel models at the mandatory data rate. For the considered channel models, system performances are evaluated for different numbers of Rake fingers, and the error correction capability of channel encoding is tested at various data rates. The results of this study are important for the implementation of the IEEE 802.15.4a standard.